Geographic variation in the skulls of the horseshoe bats, Rhinolophus simulator and R. cf. simulator: Determining the relative contributions of adaptation and drift using geometric morphometrics. Issue 22 (2nd November 2021) - Mutumi, Gregory L.; Jacobs, David S.; Bam, Lunga
Abstract: The relative contributions of adaptation and genetic drift to morphological diversification of the skulls of echolocating mammals were investigated using two horseshoe bat species, Rhinolophus simulator and R. cf. simulator, as test cases. We used 3D geometric morphometrics to compare the shapes of skulls of the two lineages collected at various localities in southern Africa. Size and shape variation was predominantly attributed to selective forces; the between‐population variance ( B ) was not proportional to the within‐population variance ( W ). Modularity was evident in the crania of R. simulator but absent in the crania of R. cf. simulator and the mandibles of both species. The skulls of the two lineages thus appeared to be under different selection pressures, despite the overlap in their distributions. Difference in the crania of R. cf. simulator was centered largely on the nasal dome region of R. cf. simulator but on the cranium and mandibles of R. simulator . It is likely that the size and shape of the nasal dome, which acts as a frequency‐dependent acoustic horn, is more crucial in R. cf. simulator than in R. simulator because of the higher echolocation frequencies used by R. cf. simulator . A larger nasal dome in R. cf. simulator would allow the emission of higher intensity pulses, resulting in comparable detection distances to that of R. simulator . In contrast, selection pressure is probably more pronounced on the mandibles and cranium of R. simulator to compensate for the loss in bite force because of its elongated rostrum. The predominance of selection probably reflects the stringent association between environment and the optimal functioning of phenotypic characters associated with echolocation and feeding in bats. Abstract : The relative contributions of adaptation and drift to morphological diversification of the crania of echolocating mammals were investigated using two horseshoe bat species, Rhinolophus simulator and R. cf. simulator, as test cases. Shape variation was predominantly attributed to selective forces. The predominance of selection probably reflects the stringent association between environment and the optimal functioning of phenotypic characters associated with echolocation and feeding in bats.